1994
DOI: 10.1042/bj3030775
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic function of human procathepsin D: the role of the propeptide

Abstract: The proform of cathepsin D is secreted by some human breast-cancer cell lines upon stimulation with oestrogen. In these cell lines, procathepsin D was described to act as an autocrine mitogen, and a correlation between the cathepsin D concentration in tumour tissues and poor prognosis for the patient was demonstrated in several independent investigations. In the present study, we focused on the mechanism of procathepsin D mitogenic activity. Procathepsin D isolated from secretions of ZR-75-1 breast-cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 29 publications
8
79
0
Order By: Relevance
“…Additional experiments showed the presence of saturable, M6P-independent binding sites. 78 The proofs of the new pathway of pCD interaction with cell membrane were further strengthened by the finding that the binding of FITC-labeled pCD to cancer cells can be inhibited by unlabeled procathepsin but only marginally by either M6P, anti -M6P-R antibodies, or by soluble M6P-R. 56,79 In addition, the biological activities of pCD cannot be blocked by anti -M6P-R antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Additional experiments showed the presence of saturable, M6P-independent binding sites. 78 The proofs of the new pathway of pCD interaction with cell membrane were further strengthened by the finding that the binding of FITC-labeled pCD to cancer cells can be inhibited by unlabeled procathepsin but only marginally by either M6P, anti -M6P-R antibodies, or by soluble M6P-R. 56,79 In addition, the biological activities of pCD cannot be blocked by anti -M6P-R antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Human cath-D is synthesized as a 52-kDa precursor that is rapidly converted in the endosomes to form an active, 48-kDa, single-chain intermediate, and then in the lysosomes into the fully active mature protease, composed of a 34-kDa heavy chain and a 14-kDa light chain (Gieselmann et al, 1985). The overexpression of cath-D in breast cancer cells leads to the hypersecretion of the 52-kDa pro-cath-D into the extracellular environment (Vignon et al, 1986;Capony et al, 1989;Fusek and Vetvicka, 1994). Cath-D affects both the cancer cells and the stromal cells of the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of cath-D expression in breast cancer cells decreases tumor growth and metastasis Ohri et al, 2007;Vashishta et al, 2007). Human secreted pro-cath-D stimulates breast cancer cell proliferation (Vignon et al, 1986;Fusek and Vetvicka, 1994;Vetvicka et al, 1994;Ohri et al, 2008), fibroblast outgrowth (Laurent-Matha et al, 2005) and angiogenesis (Hu et al, 2008). We have shown that a mutated catalytically inactive version of cath-D (D231N) is still mitogenic for tumor cells and fibroblasts (Glondu et al, 2001;Berchem et al, 2002;Laurent-Matha et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, numerous studies clearly demonstrated that pCD secreted from cancer cells serve as an autocrine growth factor for breast [180,181], prostate [182,183], ovarian [184] and lung cancer cells [185,186]. Breast cancer cells with down-regulated expression of pCD by either antisense gene transfer [187], RNA interference [188] or ribozymes [189] displayed reduced growth in vitro and in vivo.…”
Section: Cancer Cell Proliferationmentioning
confidence: 99%